Protective role of exosomes in renal ischemia-reperfusion injury: a systematic review and meta-analysis - Wang, Weibo; Tai, Supeng; Cheng, Xi; Yang, Lexing; Chang, Yifan; Yan, Junyi; Tao, Junyue; Zhou, Jun (Frontiers in Pharmacology, 2025)
IntroductionRenal ischemia-reperfusion injury (RIRI) is a major cause of acute kidney injury (AKI), commonly triggered by clinical procedures such as nephrectomy, renal transplantation, or shock resuscitation, and may progress to chronic kidney disease (CKD). Although exosomes hold promise as nanotherapeutics with pleiotropic mechanisms for renal protection, robust preclinical validation remains limited. This study aimed to clarify the therapeutic potential of exosome-based interventions for RIRI and to explore factors that modulate their efficacy.MethodsThis systematic review and meta-analysis synthesized data from 19 controlled preclinical studies involving 245 rodents, retrieved from the PubMed, Web of Science, Embase, and Cochrane Library databases, to evaluate the therapeutic efficacy of exosomes in experimental RIRI models.ResultsExosome treatment led to broad therapeutic improvements in renal function, renal damage, inflammation, oxidative stress, apoptosis, pyroptosis, cellular proliferation, and fibrosis. Subgroup analyses identified exosomal source as a critical determinant of efficacy, with mesenchymal stem cell- and endothelial colony-forming cell-derived exosomes outperforming those from fibroblasts. No clear dose-response relationship was observed, and while pre-treatment initially appeared more effective than post-treatment, this difference was not significant after adjusting for confounders. Notably, different administration routes yielded comparable therapeutic outcomes.DiscussionThese findings underscore the renoprotective potential of exosome therapy in RIRI and highlight the need for further investigation to optimize therapeutic protocols and accelerate clinical translation.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251008479, identifier PROSPERO, CRD420251008479.